Marjolin's Ulcer (A Study of 40 Cases) - Tripathi, F. M.; Khanna, Mrs. S.; Khanna, N. N.; Sinha, J. K.; Bhattacharya, V.; Bariar, L. M. (Indian Journal of Plastic Surgery, 1982)
Present series is based on 40 cases of histologically proved Marjolin's ulcer, attending Plastic Surgery Service of University Hospital B. H. U. over a period of 8 years. This tumour is fairly common in this part of India. Adolescents and adult males are commonly affected by this disease. Limbs, especially around joints are the commonest site of involvement. Marjolin's ulcer is rather slow growing malignant tumour mostly over unstable scar of burns, which is not primarily grafted. The lag period in present series is 17 years and lymph node metastasis is less common and distant metastasis is rare. Squamous cell carcinoma is the commonest histologic type and majority of patients have been treated by surgery.Celsus in the first century A.D. was the first man to describe malignant degeneration in a burn scar, however, the term Marjolin's ulcer was given to the carcinoma arising in post traumatic scar which was described for the first time by Jean-Nicholas Marjolin in the year 1828. Since then the term Marjolin's ulcer has been used for the malignant degeneration in chronic ulcers of the skin, sinuses as well as burn scars. Though the lesion described by Marjolin was not thought to be malignant by Marjolin himself, it was identified as malignant by Smith in 1850 and Da Costa (1903) used the term ‘Marjolin's ulcer’ for all such malignant lesions.